The EVOLVING ROLE OF HAEMATOLOGY NURSING PRACTICE: A CROSS-SECTIONAL SURVEY - Liptrott, Sarah; NíChonghaile, Mairéad; O’Connell, Liz; Aerts, Erik (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background and Objectives: The scope of haematology nursing practice is dynamic and must respond to advances in treatment, patients’ needs and service requirements. Little is known however, about different roles of haematology nurses across the European setting. The purpose of this study was to identify professional practices of haematology nurses. Method: A cross sectional online survey design was used to investigate practice elements undertaken by haematology nurses. Frequencies and descriptive statistics were calculated for demographic variables and chi-square tests to examine relationships between practice elements, nursing role and country. Results: Data is reported from 233 nurses across 19 countries, working as Staff Nurses (52.4%), senior nurses (12.9%) and Advanced Practice Nurses (APNs) (34.8%). Most frequently reported activities included medication administration - oral/ intravenous (90.0%), monoclonal antibodies (83.8%), chemotherapy (80.6%), and blood components (81.4%). APNs were more commonly involved in nurse-led clinics and prescribing activities (p < .001, p = .001, respectively), however other nursing groups also reported performing extended practice activities. Patient and carer education was a significant part of all nurses roles, however senior nurses and APNs were more often involved with the multidisciplinary team (p < .001) and managerial responsibilities (p < .001). Nurses involvement in research was limited (36.3%), frequently reported as an out of work hours activity. Conclusions: This study describes haematology nursing care activities being performed in a range of contexts and within different nursing roles. It provides further evidence of nursing activity and may contribute to a core skills framework for haematology nurses.